Fortificação de alimentos com ferro: verificação do atendimento à RDC nº 344/2002/ANVISA no Estado do Ceará - Melo, Cintia de Brito (2015)
Iron deficiency is the most prevalent nutritional disorder in the world. In Brazil, iron deficiency has been recognized as an important cause of anemia for more than two decades. Iron deficiency anemia sets up an epidemiological problem of great importance that has influenced the health public spending. Among the factors that contribute to this cause is the low intake of iron, influenced by poor living conditions. The iron has been used in foods widely consumed by the population as a strategy to improve the nutritional status of populations in several countries. This study was carried out to evaluate the iron content of wheat and corn flour products available in the State of Ceará through the Nutritional Content Assessment Program of Health Ministry (PATEN) in a quantitative and retrospective kind of study of iron content assessment through analysis realized by the Central Public Laboratory of Ceara State (LACEN). Thus, attempting to verify the compliance of the products sold in the state of Ceara to The Board Resolution Collegiate, RDC Nº 344/2002/ANVISA, which obligates the fortification of wheat and maize flour with iron and folic acid, as well as to compare the prevalence of iron deficiency anemia in the the last two decades in Brazil. It was concluded that approximately 58% of the samples analyzed in the last three years were considered unsatisfactory in relation to RDC No. 344/2002/ANVISA, ie having iron content of less than 4.2 mg per 100 g of flour. In turn, the prevalence of iron deficiency anemia in Brazil has not changed significantly over the last two decades, even with the mandatory fortification of flour with iron.